COVID-19 pandemic: stress and life satisfaction among parents of children with autism spectrum disorder in Malaysia / Muhamad Afif Hilmi Aznor Helmi and Mohd Suleiman Murad - Aznor Helmi, Muhamad Afif Hilmi; Murad, Mohd Suleiman (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Since the global coronavirus disease (COVID- 19) outbreak, the family of children with special needs have had difficulty to care of their children especially parents of children with autism spectrum disorder (ASD). Stress has become a persistent subject in the effect of a special needs’ child in the family, mainly the parents. Parents may experience the factors such as financial burdens or psychological difficulties resulting from this pandemic which may trigger their mental health problems. There is a substantial link between parenting stress and life satisfaction, implying that parenting stress is a predictor of life satisfaction among parents of disabled children such as ASD. This study aims to determine the relationship between stress and life satisfaction during COVID- 19 pandemic. Seventy-one parents of children with ASD in Malaysia participated in this study. Two outcome measures were used which is the Parental Stress Scale (PSS) and the Satisfaction with Life Scale (SWLS). The result reported that the total mean score of the parents of children with ASD was found to be at a high level of stress [mean= 63.5 (8.22)]. In addition, the relationship between parental stress and life satisfaction was negative, strong and significant (r=-0.805, p< 0.001). Moreover, there was a significant difference between parental stress with age and gender, where the age group (51- 60) [mean=69.30 (1.43)] and the father [mean=66.24 (5.88)] was at a higher level of stress. However, there were no significant differences between parental stress with education level, financial factors, and employment status. Stress management programs for parents especially, for older age and fathers, play a significant role in regulating emotional well-being and enhancing parent adjustment capabilities, which improve life satisfaction.